Issues in solid-organ transplantation in children: translational research from bench to bedside (Clinics, 2014)
In this review, we identify important challenges facing physicians responsible for renal and cardiac transplantation in children based on a review of the contemporary medical literature. Regarding pediatric renal transplantation, we discuss the challenge of antibody-mediated rejection, focusing on both acute and chronic antibody-mediated rejection. We review new diagnostic approaches to antibody-mediated rejection, such as panel-reactive antibodies, donor-specific cross-matching, antibody assays, risk assessment and diagnosis of antibody-mediated rejection, the pathology of antibody-mediated rejection, the issue of ABO incompatibility in renal transplantation, new therapies for antibody-mediated rejection, inhibiting of residual antibodies, the suppression or depletion of B-cells, genetic approaches to treating acute antibody-mediated rejection, and identifying future translational research directions in kidney transplantation in children. Regarding pediatric cardiac transplantation, we discuss the mechanisms of cardiac transplant rejection, including the role of endomyocardial biopsy in detecting graft rejection and the role of biomarkers in detecting cardiac graft rejection, including biomarkers of inflammation, cardiomyocyte injury, or stress. We review cardiac allograft vasculopathy. We also address the role of genetic analyses, including genome-wide association studies, gene expression profiling using entities such as AlloMap®, and adenosine triphosphate release as a measure of immune function using the Cylex® ImmuKnow™ cell function assay. Finally, we identify future translational research directions in heart transplantation in children.